Determinants of non-performing loans in Bhutanese financial sector - TSHERING, Ugyen (KDI School, 2016)
This paper attempts to study the internal (bank specific) and external (macroeconomic) determinants of non-performing loans (NPLs) in Bhutanese financial sector using a panel data and random effect model. This study uses the data from a panel of 4 financial institutions (3 banks and 1 insurance company) engaged in lending activities and macroeconomic data covering for period from 2005 to 2014. Of the macroeconomic variables used (GDP, Unemployment rate, Inflation rate), the empirical result indicates that only GDP significantly affect the NPLs and is negatively related with the NPLs. However, contrary to most of the previous studies, the empirical analysis do not support the view that higher unemployment in the economy will lead to higher NPLs. Inflation rate is also not statistically significant and does not affect NPLs in Bhutanese financial sector. Regarding the bank specific variables, the results indicate that all variables are statistically significant in explaining the variation of NPLs. The bank specific variables used for this study are ROA, ROE, CAR, Bank Size and Loans to Asset ratio. The result indicates a negative relationship of NPLs to ROE and CAR while indicating positive relationship to ROA, Bank Size and Loans to Asset ratio.
Thesis(Master) --KDI School:Master of Public Policy,2016